STRATEGI PROMOSI DALAM MENINGKATKAN LOYALITAS KONSUMEN PADA MINIMARKET BASMALAH DI KABUPATEN JEMBER - Raharto, Eko; Supriyanto; Dienillah, Izzah (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
This study aims to reveal the importance of promotion in increasing the interest of purchasing decisions and consumer loyalty at minimarket al Mubarok in Jember district. In this study it is revealed that promotion has a positive significance on and consumer loyalty at Basmalah minimarket in Jember district. This study aims to examine and analyze whether promotion affects purchasing decisions and consumer loyalty at Basmalah minimarkets in Jember district. The research was conducted at the Basmalah minimarket in Jember district by taking a sample of 100 consumers. This study uses an explanatory research approach or confirmatory research, namely research that explains the causal relationship and tests the relationship between several variables through hypothesis testing or explanatory research. The sampling method in the study was accidental sampling method. Data collection techniques using interviews, observations, documentation and questionnaires. Validity and Reliability of Instruments using Validity Test and Reliability Test. Data Analysis Methods using Path Analysis, Classical Assumption Test, Multicolonierity, Heterokesdasticity, Normality Test, t Test, and Counting Paths. The results showed that the right promotion strategy can increase the profit of Basmalah minimarket.